Existing plagiarism detection techniques - Eisa, Taiseer Abdalla Elfadil; Salim, Naomie; Alzahrani, Salha (Online information review, 2015)
Purpose – The purpose of this paper is to analyse the state-of-the-art techniques used to detect plagiarism in terms of their limitations, features, taxonomies and processes. Design/methodology/approach – The method used to execute this study consisted of a comprehensive search for relevant literature via six online database repositories namely; IEEE xplore, ACM Digital Library, ScienceDirect, EI Compendex, Web of Science and Springer using search strings obtained from the subject of discussion. Findings – The findings revealed that existing plagiarism detection techniques require further enhancements as existing techniques are incapable of efficiently detecting plagiarised ideas, figures, tables, formulas and scanned documents. Originality/value – The contribution of this study lies in its ability to have exposed the current trends in plagiarism detection researches and identify areas where further improvements are required so as to complement the performances of existing techniques.